The Path to microRNA Therapeutics in Psychiatric and Neurodegenerative Disorders - Chan, Anthony W.; Kocerha, Jannet (Frontiers in Genetics, 2012)
The microRNA (miRNA) class of noncoding RNAs exhibit a diverse range of regulatory roles in neuronal functions that are conserved from lower vertebrates to primates. Disruption of miRNA expression has compellingly been linked to pathogenesis in neuropsychiatric and neurodegenerative disorders, such as schizophrenia, Alzheimer’s Disease, and Autism. The list of transcript targets governed by a single miRNA provide a molecular paradigm applicable for therapeutic intervention. Indeed, reports have shown that specific manipulation of a miRNA in cell or animal models can significantly alter phenotypes linked with neurological disease. Here, we review how a diverse range of biological systems, from rodents to primates such as monkeys and humans, can be integrated into the translation of miRNAs as novel clinical targets.